3D Framework and Supramolecular Structures Assembly from a Carboxyphosphonic Acid and Transition Metals: Sensing of Nitro Compounds and Surface Photovoltage Properties. Issue 21 (21st December 2016) - Zhu, Yanyu; Wang, Tingting; Su, Yuming; Sun, Zhengang; Dong, Dapeng; Cai, Xiao'ou; Sun, Hongmei; Li, Jing
Abstract: Three new metal carboxyphosphonates with 3D framework and supramolecular structures, namely, [Zn(H4 L)2 ] (1 ), [Cu2 (HL)(H2 O)2 ] (2 ) and [NH(CH2 )4 NH]0.5 [Cu(H3 L)] (3 ) (H5 L=4‐HOOC‐C6 H4 ‐CH2 N‐(CH2 PO3 H2 )2 ), have been synthesized under hydrothermal conditions. For compound1, ZnO6 and CPO3 polyhedra are interconnected into a 2D layer via corner‐sharing, which is further assembled into a 3D supramolecular structure through π‐π stacking interactions. Compound2 exhibits a 3D framework structure. The interconnection of CuO4 N, CuO5 polyhedra and CPO3 tetrahedra via corner‐sharing forms a 2D inorganic layer. These inorganic layers are further linked via the organic backbone −C6 H4 CH2 N(CH2 )2 − of the carboxyphosphonate ligands, generating a 3D framework structure. In compound3, two CuO4 N polyhedra and four CPO3 tetrahedra are interconnected into a unit, and then these units are further connected into a 1D infinite chain via corner‐sharing. Neighboring chains are assembled into a 2D layered structure through hydrogen bond interactions between the nitrogen atoms from piperazine and uncoordinated phosphonate oxygen atoms. Then, such layers are further assembled into a 3D supramolecular network via interlayer hydrogen bonds. Compound1 has been realized for the sensitive sensing of 4‐nitrophenol (4‐NP) by luminescence quenching method in the liquid phase. Surface photovoltage properties of compounds2 and3 have been investigated. Abstract : Three transition metal carboxyphosphonates with 3D framework and supramolecular structures have been hydrothermally synthesized. Compound1 has been realized for the sensitive sensing of 4‐nitrophenol (4‐NP) by luminescence quenching method in the liquid phase. Surface photovoltage properties of compounds2 and3 have been investigated.